Saturating Light Induces Sustained Accumulation of Oil in Plastidal Lipid Droplets in Chlamydomonas reinhardtii. Issue 4 (13th June 2016) - Goold, Hugh Douglas; Cuiné, Stéphan; Légeret, Bertrand; Liang, Yuanxue; Brugière, Sabine; Auroy, Pascaline; Javot, Hélène; Tardif, Marianne; Jones, Brian; Beisson, Fred; Peltier, Gilles; Li-Beisson, Yonghua
Abstract : Saturating light induces oil storage in Chlamydomonas reinhardtii, and the newly formed oil accumulates in lipid droplets distinct in protein and lipid compositions from those induced by nitrogen starvation. Abstract: Enriching algal biomass in energy density is an important goal in algal biotechnology. Nitrogen (N ) starvation is considered the most potent trigger of oil accumulation in microalgae and has been thoroughly investigated. However, N starvation causes the slow down and eventually the arrest of biomass growth. In this study, we show that exposing a Chlamydomonas reinhardtii culture to saturating light (SL ) under a nonlimiting CO2 concentration in turbidostatic photobioreactors induces a sustained accumulation of lipid droplets (LD s) without compromising growth, which results in much higher oil productivity than N starvation. We also show that the polar membrane lipid fraction of SL -induced LD s is rich in plastidial lipids (approximately 70%), in contrast to N starvation-induced LD s, which contain approximately 60% lipids of endoplasmic reticulum origin. Proteomic analysis of LD s isolated from SL -exposed cells identified more than 200 proteins, including known proteins of lipid metabolism, as well as 74 proteins uniquely present in SL -induced LD s. LD s induced by SL and N depletion thus differ in protein and lipid contents. Taken together, lipidomic and proteomic data thus show that a large part of the sustained oil accumulation occurring under SL is likely due to the formation of plastidial LD s. We discuss our data in relation to the different metabolic routes used by microalgae to accumulate oil reserves depending on cultivation conditions. Finally, we propose a model in which oil accumulation is governed by an imbalance between photosynthesis and growth, which can be achieved by impairing growth or by boosting photosynthetic carbon fixation, with the latter resulting in higher oil productivity.